Is the long case dead? 'Uh, I don't think so': the Uh/Um Index. Issue 12 (December 2016) - Duvivier, Robbert; Veysey, Martin
Abstract: Current tools for clinical assessment are tedious and time‐consuming, particularly the dreadful long case. There is a need for novel instruments that incorporate other aspects of competence. We propose such a method, namely the Uh/Um Index. Our innovation paper describes the rationale for using speech dysfluency and occurrences of filler words such as 'uh' and 'um' as a proxy for competence. This appears to have won initial support from senior clinicians in our institution. Additional research is needed (non‐restricted grants are welcomed) to establish rigorous standard setting and to fund our attendance at overseas conferences to make the Uh/Um Index the new buzzword in medical education. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.